Metric Subregularity for a Multifunction (Journal of Mathematical Study, 2021)
Metric subregularity is an important and active area in modern variationalanalysis and nonsmooth optimization. Many existing results on the metric subregularitywere established in terms of coderivatives of the multifunctions concerned. Thisnote tries to give a survey of the metric subregularity theory related to the coderivativesand normal cones.
Keywords: Metric subregularity; coderivative; normal cone.